PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAPKINERJAANGGOTA POLRI PADA PAMPERSLOG DITPOLUDARA KORPOLAIRUD BAHARKAM POLRI - Siti Ubaidah; Rafael Rafael (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2018)
he research aims to look at the Effect of Organizational Culture and Leadership on the Performance of Polri Members on Pamperslog Ditpoludara Sub-Directorate Korpolairud Baharkam Polri, From the results of the research as follows: The purpose of this study was to determine the influence of organizational culture and leadership on the performance of Polri Members on Pamperslog Sub Directorate Ditpoludara Korpolairud Baharkam National Police The research method used is the survey method. The research respondents were 58 members taken by census. The technique of collecting data using a questionnaire. Data analysis using simple and multiple correlations, as well as simple linear regression techniques and multiple regression. The results showed that the results of multiple regression tests simultaneously both independent variables (organizational culture and leadership) had a significant effect on organizational culture variables. But partially it shows that only 1 variable (leadership) that has a significant effect on Police Members on the Pamperslog Sub Directorate of the Police Directorate of Korpolairud Baharkam Polri. Thus making the leadership variable as the dominant variable in this study. Based on these findings, the application of organizational culture in the Pamperslog Ditpoludara Sub-Division, Korpolairud Baharkam Polri needs to be improved by encouraging each Member’s activities to apply organizational cultural values that have been applied in the work environment so as to improve the performance of Members. And try to accommodate new cultural values that promise the progress of the organization and abandon organizational cultural values that do not support the development of member performance. The leader must also show commitment to his organization and set an example and be a role model in implementing organizational values.